Bioeconomic analysis of Norwegian reindeer husbandry in the face of crowberry encroachment - Pham, Minh Nhat (UiT The Arctic University of Norway, 2025)
Allelopathic encroachment of Empetrum nigrum (crowberry) is impacting the Norwegian reindeer husbandry. This thesis first explores both the negative and positive impacts of crowberry, and then analyses the effect of its encroachment on the husbandry under climate change. The thesis consists of four papers, one qualitative study conducting systematic literature review of Empetrum nigrum , and three quantitative studies applying the method of bioeconomic modeling. The first paper categorizes the benefits and detriments of crowberry using three different nature assessment concepts, and finds mixed impacts on the local socioecological system, particularly eight benefits and three detriments. Focusing on the detrimental impacts of crowberry, the three quantitative papers develop various versions of the reindeer bioeconomic model, including three stocks – vegetation, crowberry, and reindeer – along with two primary adaptive measures: reindeer feeding and crowberry control. The second paper applies static optimization and concludes that controlling crowberry alongside reindeer feeding can mitigate the negative impacts of encroachment. The third paper extends the analysis to dynamic optimization, confirming the importance of controlling crowberry to maintain high quality grazing pasture and reindeer population over time. Using optimal control theory, the fourth paper explores a specific yet neglected benefit of crowberry – carbon sequestration – and demonstrates that with this beneficial value, the optimal efforts to control crowberry should be less than in scenarios without. The thesis hence underscores several policy implications. Firstly, adoption of the Nature’s Contribution to People (NCP) concept may be embraced to provide a comprehensive perspective. Secondly, the socio-ecological system of the husbandry is impacted negatively by crowberry encroachment through deteriorating grazing pastures. Thirdly, while supplementary feeding can increase reindeer numbers, it does not address the ecological issues of pasture ...